2015
DOI: 10.1097/mpa.0000000000000178
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Alterations in Expression and Subcellular Localization of MUC1 in Pancreatic Ductal Carcinogenesis in Syrian Hamsters

Abstract: Alterations in the expression and subcellular localization of MUC1 represent a biphasic phenomenon, and the latter may be associated with EMT in pancreatic carcinogenesis in hamsters, which indicates that changes in MUC1 are important targets for pancreatic cancer prevention and chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…This study found that MUC1 is a key molecule for cell proliferation and invasion of PDAC by regulating apoptosis and ROS production. The significance of MUC1 in PDAC has been reported that its increased expression in cancer is an indicator of malignancy, and that it is involved in cell proliferation, angiogenesis, changes in life expectancy due to methylation, and enhanced efficacy of drugs, making it valuable as a diagnostic marker and therapeutic target [11,12,[18][19][20]. However, no treatment has been established that directly targets MUC1.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that MUC1 is a key molecule for cell proliferation and invasion of PDAC by regulating apoptosis and ROS production. The significance of MUC1 in PDAC has been reported that its increased expression in cancer is an indicator of malignancy, and that it is involved in cell proliferation, angiogenesis, changes in life expectancy due to methylation, and enhanced efficacy of drugs, making it valuable as a diagnostic marker and therapeutic target [11,12,[18][19][20]. However, no treatment has been established that directly targets MUC1.…”
Section: Discussionmentioning
confidence: 99%